“Dante… Bruno. Vico.. Joyce:” Samuel Beckett’s “identified contraries” - Julie BÉNARD (E-REA)
This article deals with Samuel Beckett’s first essay “Dante… Bruno. Vico.. Joyce” which was published in the avant-garde magazine transition in 1929 at a time when modernism was itself becoming tradition. If Beckett’s critical writing praises one of the modernist champions, James Joyce, it also feeds on other arts, such as cinema and its relation to ideographic writing, as well as on more questionable sources such as the science of the occult. By so doing, Beckett goes against the established avant-garde, whether they are they are writers or critics. I argue that Beckett borrows from the writings of Italian philosopher Giordano Bruno to shape his own literary principle, that of “identified contraries,” proposing a formula without imposing a programme. This propels him to the heart of three modernist principles: “historical modernism”, “hieroglyphic modernism” and “alchemical modernism.” This article means to explore them in the light of Beckett’s essay.